Biological sex differences in fatigue in resistance-trained individuals: A scoping review - Amdi, Christian Houmann; Fyfe, Jackson; Yoon, SangHoon; Nuckols, Greg; Refalo, Martin (International Journal of Sports Medicine, 2025)
Females may experience less neuromuscular fatigue and improved recovery following resistance training than males; however, it is unclear whether this applies to resistance-trained individuals. A systematic scoping review was performed to map the evidence on sex differences in fatigue during and following resistance training in trained participants. PubMed, CINAHL and SPORTDiscus were searched following PRISMA-ScR guidelines. The protocol was prospectively registered. Of the 4,020 identified articles, 34 were included. These studies assessed sex differences in fatigue using various measures during single and multiple resistance training sets, performance relative to the baseline at various time points (0–5 min, 1–6 h, 24 h, and 48–96 h after resistance training), and metabolic responses. Substantial heterogeneity in study design and results were observed. Together, most studies found minor-to-no sex differences in neuromuscular fatigue, but some evidence of greater fatigability in males during or immediately following resistance training were found when (1) more complex free-weight exercises were performed with moderate loads, (2) rest periods were shorter, and (3) males were substantially stronger than females in relative terms, among others. Future investigations should explore the impact of training variables and habitual training on fatigue in males and females of comparable relative strength and technical proficiency.
Keywords: fatigue; sex differences; resistance training